Crystal structure of Al-rich fluorophlogopite, K1.0(Mg2.8Al0.2)(Si2.8Al1.2)O10F2 - Aiqing Chen; Lixue Zhang (Zeitschrift für Kristallographie - New Crystal Structures)
K1.0(Mg2.8Al0.2)(Si2.8Al1.2)O10F2, monoclinic, C2/m (no. 12), a = 5.3040(11) Å, b = 9.2288(18) Å, c = 10.1286(20) Å, β = 100.173(3)°, V = 488.00(17) Å3, Z = 2, Rgt(F) = 0.0387, wRref(F2) = 0.1086, T = 298 K.